NEW TECHNOLOGIES AND TECHNIQUES IN THE CONSTRUCTION OF OJSC "KYIVMETROBUD" COMPLEX OBJECTS - Petrenko, V. I. (Science and Transport Progress, 2010)
In the article the results of wide introduction of new technologies and technique in construction of difficult objects by the Kievmetrostroy are presented.